Quebra de sigilo pelas Comissões Parlamentares de Inquérito - Porto Filho, Pedro Paulo de Rezende (2007)
The scientific works on congressional investigating committees increase in a geometrical progression lately, as far as they have become the main Legislative Power activities. Analyzing the existing reports and some court judgments about congressional investigating committees, we identify the need to elaborate a work that could bring indispensable requirements and guarantees to be observed by these committees with regards to secrecy violation. Among them, we point out (i) the due process of law and the principle of collegiate; (ii) the congressional investigating committees action motivation duty; (iii) to assure the adversary system and full defense; (iv) the principle of proportionality; (v) the restrictive measure exception; (vi) the binding effect of the requirement terms. Finally, we clarify that the congressional investigating committees actions, besides being strictly tied to these requirements and principles, are also subject to Judiciary Power previous and posterior monitoring, emphasizing that most of the time they affect and restrict fundamental guarantees